Managing Menu and Culinary Offerings as a Cannelé Dining Scene at The Mulia, Mulia Resort & Villas - Wenten, I Wayan; Ernawati, Ni Made; Mudana, I Gede; Suparta, I Ketut (Badan Riset dan Inovasi Daerah Provinsi Bali, 2025)
Purpose: The purpose of this research is the demand for popular patisserie products in Bali, which prompted The Mulia, Mulia Resort & Villas, Nusa Dua, Bali to establish Cannelé as their additional dining outlet to offer exquisite patisserie offerings. Research methods: The study employs a POAC-based approach (planning, organizing, actuating, and controlling) supported by theories in Gastronomy, Menu Engineering, and Gastronomic Culinary. This study employs a qualitative approach, collecting data through observation, document study, interview, and focus group discussion. Findings: The Mulia, Mulia Resort & Villas develop and manage Cannelé through POAC management cycle. Menu management was conducted rigorously through menu engineering and trend analysis to classify items based on sales performance for operational analysis. The model that can be designed and applied is the operational management cycle. The comparison of menu categories shows a strong foundation for items in the Star and Plow horse and potential to the Puzzle. A significant number of items fall in dog categories. Patisserie/cake product line, ice cream, and coffee show the strongest performance. Meanwhile, the savory menu/main dishes and kids’ menu demonstrate low sales. Implication: This study contributes valuable applied knowledge in culinary management and hospitality tourism, particularly in F&B product strategy within luxury hotel environments.